The Habituation of Ubudiyah Activities as an Instrument for Strengthening Students’ Spiritual and Social Competencies - Sholihul Anshori; Hanifuddin (Journal Of Islamic Education And Pesantren, 2024)
This study aims to analyze the habituation of ubudiyah activities as an instrument for strengthening students’ spiritual and social competencies within the context of Islamic education. The study employed a qualitative approach with a phenomenological orientation using a case study design. The research was conducted at SMK Sultan Agung 2 Diwek Jombang, involving purposively selected participants consisting of the principal, Islamic Education teachers, and students who were directly engaged in ubudiyah activities. Data were collected through in-depth interviews, participant observation, and documentation, and were analyzed thematically using phenomenological analysis procedures. The findings indicate that the habituation of ubudiyah activities is experienced by students as a gradual and reflective process of value internalization that simultaneously strengthens spiritual and social competencies. Spiritual competence develops through increased worship awareness, inner calmness, and religious value orientation, while social competence is fostered through religious discipline, self-confidence, empathy, and social interaction within collective religious activities. This study highlights that ubudiyah habituation serves as an experiential pedagogical practice that contributes significantly to holistic character development.